ANALISA SIFAT MEKANIK PADUAN ALUMINIUM SILIKON METAL DENGAN VARIASI CAMPURAN - Fadly Ahmad Kurniawan Nasution; Ade Irwan (Universitas Harapan Medan, 2019)
when aluminum is exposed to free air. This aluminum oxide layer prevents further oxidation. One way of recycling (recycle) is the smelting process. Where adding Silicon Metal to the Aluminum alloy makes these two alloys strong and light Aluminum-Silicon Metal is cast with 3 ratios namely (92% Al: 8% Si, 90% Al: 10% Si, 88% Al: 12% Si) shaft shape. After finishing casting the specimen is turned with ASTM E8 size followed by tensile testing to get the stress value, strain value and elastic modulus value in the material. The addition of Silicon Metal elements in Aluminum, the tensile strength of Aluminum will be even smaller. Crust/dirt is one of one reason for the decrease in tensile strength. This crust/dirt can also cause defects in the casting specimens. The amount of porosity that occurs in casting aluminum alloys does not only depend on the amount of hydrogen gas absorbed by the metal, but also depends on the speed of solidification of the metal in the mould. From the test results, the average stress value for a mixture of Al 92% - Si 8% is 0.378697366 MPa, a mixture of Al 90% - Si 10% is 0.386266797 Mpa, a mixture of Al 88% - Si 12% is 0.14015392 MPa.